2010
DOI: 10.1182/blood-2010-06-289850
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of platelet myosin light chain (MYL9) by RUNX1: implications for thrombocytopenia and platelet dysfunction in RUNX1 haplodeficiency

Abstract: Mutations in transcription factor RUNX1 are associated with familial platelet disorder, thrombocytopenia, and predisposition to leukemia. We have described a patient with thrombocytopenia and impaired agonist-induced platelet aggregation, secretion, and glycoprotein (GP) IIb-IIIa activation, associated with a RUNX1 mutation. Platelet myosin light chain (MLC) phosphorylation and transcript levels of its gene MYL9 were decreased. Myosin IIA and MLC phosphorylation are important in platelet responses to activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 49 publications
3
59
0
Order By: Relevance
“…The arrest of endomitosis is linked to MK maturation and RUNX1 has a role in this process by regulating genes involved in platelet functions, including myosin light chain 9 (MYL9/MLC2) 22 24,25 suggesting that RUNX1 could also regulate the switch from mitosis to endomitosis by targeting MYH10. Using an in silico approach with the ChipMapper online software, we identified a putative conserved RUNX1 transcription factor-binding site in the MYH10 promoter region (Fig.…”
Section: Runx1 Mediates Myh10 Silencing During Mk Differentiationmentioning
confidence: 99%
“…The arrest of endomitosis is linked to MK maturation and RUNX1 has a role in this process by regulating genes involved in platelet functions, including myosin light chain 9 (MYL9/MLC2) 22 24,25 suggesting that RUNX1 could also regulate the switch from mitosis to endomitosis by targeting MYH10. Using an in silico approach with the ChipMapper online software, we identified a putative conserved RUNX1 transcription factor-binding site in the MYH10 promoter region (Fig.…”
Section: Runx1 Mediates Myh10 Silencing During Mk Differentiationmentioning
confidence: 99%
“…RUNX1 also directly regulates the expression of myosin light chain 9 (MYL9) in megakaryocytes. Thus, downregulation of MYL9 due to RUNX1 haploinsufficiency could affect abnormal platelet production and function [31]. Platelet storage pool deficiency and low levels of MPL receptor expression have also been reported [25,32].…”
Section: Mechanism Of Thrombocytopeniamentioning
confidence: 99%
“…It was recently suggested that the MYL9 gene is a direct target of RUNX1 and provides a mechanism for decreased platelet MYL9 expression, myosin light chain (MLC) phosphorylation, thrombocytopenia, and platelet dysfunction associated with RUNX1 mutations (Jalagadugula et al, 2010). However, the functions of MYL9 in blood cells have not yet been clarified.…”
Section: Introductionmentioning
confidence: 99%